RESPONSE OF ADMINISTRATION OF TRICHOCOMPOST AND ECO ENZYME SOIL IMPROVEMENT ON GROWTH AND PRODUCTION OF GLASS GEM CORN (Zea mays L.) - May Ryan Sandi; Asmanizar; Syamsafitri (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
The main objective of this research is to determine the growth response and production of glass gem corn plants (Zea mays L.) using trichocompost soil amendments and the application of eco enzyme. This research used a factorial randomized block design (RAK) consisting of 2 treatment factors with 16 combinations and 3 replications to obtain a total of 48 plots. The parameters observed in this study were Vegetative Growth which consisted of flower age, plant height, number of leaves, root length, leaf area, stem diameter, net assimilation rate, fresh and dry root weight, shoot fresh and dry weight, plant growth rate. . The second observation is production which consists of cob length, cob diameter, cob weight per sample, cob weight with sample husks/plants. The research results showed that the results of the analysis of trichocompost fertilizer content were Nitrogen 1.93%, P2O5 1.93%, K2O 3.56; C-Organic 25.35%; Cu 23.29 Ppm, Fe 0.23%, Mn 181.95 Ppm, Zn 0.01 Ppm, pH 8.71, and water content of 50.50%. Furthermore, the results of the analysis of the eco enzyme fertilizer content are Nitrogen 0.25%, P2O5 0.02, K2O 0.04; C-Organic 0.93%; Cu >0.0002 Ppm, Fe 34.44 Ppm Mn 4.43 Ppm, Zn 0.01 Ppm, pH .25. The use of fruit waste as liquid organic fertilizer and cow dung as organic fertilizer is effectively used to increase the growth rate and productivity of corn plants, especially galss gem corn.